Lipid peroxidation and generation of hydrogen peroxide in frozen-thawed ram semen supplemented with catalase or Trolox - Sicherle, C. C. [UNESP]; Maia, M. S.; Bicudo, Sony Dimas [UNESP]; Rodello, L. [UNESP]; Azevedo, H. C. (Elsevier B.V., 2011)
Semen manipulation and cryopreservation-thaw procedures may accelerate the generation of reactive oxygen species (ROS). Sperm exposure to large amounts of ROS has been shown to cause membrane lipid peroxidation and cellular injury to the sperm. The objective of this study was to overcome the ROS production in frozen-thawed ram semen by the addition of the antioxidants catalase or Trolox to semen following thawing. Frozen-thawed ram semen (100 x 10(6) sperm/straw) was supplemented with PBS (control group), 100 mu g/ml catalase, or 100 mu M Trolox/10(8) sperm (catalase and Trolox being dissolved in PBS) and incubated (37 degrees C) for 5 min. Under the experimental conditions used in this study, the catalase and Trolox antioxidants failed to protect the sperm from the spontaneous production of ROS. However, when lipid peroxidation was induced by iron (FeSO(4)), the addition of Trolox promoted a reduction (P < 0.05) in the formation of TBARS in the semen, compared to the control and catalase semen samples. The generation of TBARS and H(2)O(2) occurred in the extender alone, without the presence of sperm cells. In conclusion, the addition of Trolox to frozen-thawed ram semen could be beneficial as it decreases the production of TBARS when oxidative stress is induced. It is possible that a longer incubation period could lead to different results. The concentration of catalase also needs to be further evaluated. The extender could contribute to the oxidative stress of sperm, as it is a source of ROS during the cryopreservation of semen. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Lipid peroxidation; Catalase; Trolox; Semen cryopreservation; Ram